135k views
1 vote
(-2p⁻⁵q . 4p⁵q⁻³)²

Explain with steps

1 Answer

3 votes

Answer:


(64)/(q^(4))

or


64q^(-4)

Explanation:

Remember the properties

Product rules


a^(n) a^(m)=a^(n+m)

Power rules


(a^(n))^(m)=a^(n*m)

we have


(-2p^(-5)q4p^(5)q^(-3))^(2)

Applying the product rules


(-2(4)p^(-5+5)q^(-3+1))^(2)


(-8p^(0)q^(-2))^(2)


(-8q^(-2))^(2)

Applying the power rules


64q^(-4)


\mathrm{Apply\:exponent\:rule}:\quad \:a^(-b)=(1)/(a^b)


64q^(-4)=(64)/(q^(4))

User Ben Lin
by
5.6k points